The Genetic Drift of Indonesian Avian Influenza A H5N1 Viruses During 2003-2008 - NI LUH PUTU INDI DHARMAYANTI; GINA SAMAAN; FERA IBRAHIM; RISA INDRIANI; . DARMINTO; AMIN SOEBANDRIO (Microbiology Indonesia, 2011)
The avian influenza A H5N1 outbreaks started in 2003 and Indonesia introduced a vaccination campaign in 2004 to control the disease. In 2007, anecdotal reports about reduced vaccine effectiveness were received from commercial farmers. This paper describes the evolution of viruses in Indonesia up till 2008 and focus on viruses from vaccinating farms reporting vaccine failure were compared to viruses isolated from outbreak areas with no vaccination program. Result of the study revealed that viruses from vaccinated chickens had more extensive mutation at the HA molecule compared to chicken and other avian species without vaccination. Substitutions occurred at the HA gene level as well as at NA, M1 and NS1 genes. Viruses isolated and characterized form 2008 vaccinated flocks had substitutions that were unique and different with the old viruses. The recommendation arising from this study to the avian influenza disease control program in Indonesia is that continuous monitoring of genetic character of viruses and the vaccine seed strain should be updated periodically and matched with the virus circulated in the field.